Stress Levels of Premature Babies in Newborn Intensive Care Units: A Comparatıve Study in Hıgh/Low Light and Sound Environment - Esra Ertürk Tosun; Emine Geçkil (Çocuk Dergisi)
Objective: The aim of this study is to examine and compare the stress levels of premature babies in high and low light and sound environments in a Neonatal intensive care unit (NICU). Materials and Methods: This descriptive comparative study was conducted in the NICU of a university hospital between 2018-2019. The sample consists of 67 premature babies who had been hospitalized in the NICU and were born between 28-37 weeks of gestation. Data were collected with a baby information form and the Newborn Stress Scale. The data were analyzed with the t test, Wilcoxon signed-rank test, Mann-Whitney U test, and Kruskal-Wallis test over dependent groups, with a p < .05 being considered significant. Results: Of the premature babies, 50.7% were found to be male and 62.7% to have been born between 33-37 weeks of gestation. The babies’ mean stress score (4.48 ± 2.52) in the high light and high noise environment was determined to be significantly higher than their mean under low light and noise levels (1.03 ± 1.95; p = .000). The infants’ average respiratory rate (54.37 ± 12.62) under high light and sound levels were found to be significantly higher than their average in low light and low sound environments (51.25 ± 9.85; p = .03). Stress levels were found to be significantly higher in premature babies whose mothers were not involved in their care and whose gestational age was between 28-32 weeks, and who’d been hospitalized in the 3rd-level unit in a high light and high sound environment (p < .05). Conclusion: The results of the study show the high light and high sound environment in the NICU to have caused stress in premature babies.